Parametric study of droplet wettability under electric field - Wang, Chenweiyi (2017)
Electrowetting is a phenomenon that used to explain how the wettability of liquid on solid surface can be controlled via applying voltage. Such liquid is extracted with very minor amount to test on the various surfaces. In this project, we intend to investigate whether the substrates are suitable for the droplets to perform under low voltages.